Increasing Customer Repurchase Intention: The Significance of Product Quality, Viral Marketing, and Customer Experience - Maribeth Adela; Meylani Tuti (APTISI Transactions on Management (ATM), 2024)
This study aims to ascertain how repurchase intention is impacted by product quality, viral marketing, and customer experience. The study population con- sists of customers who have made repeat purchases. A purposive sampling tech- nique is employed, yielding a sample size of 254 individuals and collecting data on customers with recurring transactions. Utilizing SmartPLS, the data analysis method involves a structural equation model. The findings of the study demon strate that the three independent variables customer experience, viral marketing, and product quality significantly influence the dependent variable, repurchase intention. Implementing viral marketing strategies to launch products has suc- cessfully attracted repeat business from customers. Additionally, the experience of consuming the product and the quality of the product itself can also trigger consumers to make repeat purchases. These results underscore the importance of marketing strategies that focus on product quality and customer experience, as well as the effectiveness of viral marketing in enhancing customer loyalty through increased repurchase intentions.